The PLANES model for unresectable hepatocellular carcinoma treated with transcatheter arterial chemoembolization plus lenvatinib and PD-1 inhibitors: a multicenter, retrospective study - Ya, Houxiang; Wang, Kai; Wu, Jiayi; Wu, Junyi; Zeng, Zhenxin; Li, Yinan; Ou, Xiangye; Song, Huachun; Yan, Maolin; Li, Shuqun (Frontiers in Immunology, 2026)
BackgroundThe triple therapy regimen of transcatheter arterial chemoembolization (TACE) plus lenvatinib and PD-1 inhibitors plays a significant role in the treatment of unresectable hepatocellular carcinoma (uHCC). However, only a subset of patients can benefit from it, making it crucial to screen for those who may benefit from the triple therapy regimen. This study constructed and assessed a survival prediction nomogram for uHCC patients undergoing first-line triple therapy.MethodsUsing retrospective data from 277 consecutive triple-therapy patients (treated at six Chinese centers between 2018–2023), we constructed the nomogram based on multivariate-derived predictors. Model performance was quantified through discrimination metrics and bootstrapped internal validation. External validation employed an independent cohort (n=208) from three additional institutions.ResultsIndependent predictors of overall survival (OS) included alpha-fetoprotein (AFP), maximum tumor diameter, tumor number, extrahepatic metastasis, and platelet-to-lymphocyte ratio (PLR). A PLANES model was constructed to predict 12-, 24-, and 36-month OS. The model demonstrated robust discriminative performance, with area under the curve (AUC) values of 0.887, 0.793 and 0.749 for 12-, 24-, and 36-month OS in the training cohort, respectively. External validation yielded AUCs of 0.922, 0.760, and 0.722 for corresponding time points.ConclusionsThe PLANES model was successfully established and validated for predict prognosis in unresectable HCC patients receiving first-line triple therapy.